Analisis Kebutuhan Pengembangan Monopoli Sebagai Media Pembelajaran Pada Materi Sistem Koordinasi - Nada Raudathul Rahmi; Heffi Alberida (Al-Alam: Islamic Science Education Journal, 2026)
This study aims to analyze the need for developing an educational Monopoly game as a learning media for the Coordination System topic at SMA N 1 Lubuk Alung. This research employed a descriptive method with both quantitative and qualitative approaches. The participants consisted of one Biology teacher and 32 Grade XI students. Data were collected through interviews and questionnaires, then analyzed descriptively. The results indicate that learning is still dominated by teacher explanations (55.6%), and students experience difficulties due to complex material (40.7%) and heavy memorization demands (29.6%). In addition, students show interest in game-based media (22.2%) and prefer Game-Based Learning (29.6%). These findings suggest a need for interactive learning media that can visualize abstract concepts and enhance student engagement. Therefore, the development of an educational Monopoly game is considered relevant to improve students’ understanding and participation in learning the Coordination System topic.